Effect of Sediment Size in Hydraulic Turbine Material: A Case Study of Roshi Khola in Nepal - Poudel, Laxman (Nepal Journal of Science and Technology, 2013)
Siltation problem in Nepal is major and challenging in hydropower development. It degrades the reservoir capacity and hydraulic turbines’ efficiency. Many researches have been carried out in this field and have proven sand as major substance that erodes the turbine material, but only few researches have accounted every parameters of sand on degradation of hydraulic turbines. This paper accounts size of sediments important parameter that has direct impact on turbine material. Sediment size impact has been studied firstly by characterizing size into six layered using sieve analyzer and testing its impact using high velocity test rig at Kathmandu University. Sand samples from 20 different stations of Roshi river were collected and tested on turbine material 18Cr4Ni. It found that greater micron sizes of sediments have great impact was than relatively smaller ones. It is depicted that 300-400 micron size sediment, have highest impact with weight loss of 0.022 milligram, 212-300 micron size has 0.013 milligram weight loss, 90-212 micron size has 0.012 and below 90 micron sizes have 0.0075 milligram of weight loss. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 129-132 DOI: http://dx.doi.org/10.3126/njst.v13i2.7725